1989
DOI: 10.1111/j.1365-2958.1989.tb00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the outJ gene involved in pectate lyase secretion by Erwinia chrysanthemi

Abstract: The phytopathogenic enterobacterium Erwinia chrysanthemi secretes a number of enzymes involved in plant-tissue degradation, notably the five isoenzymes of pectate lyase. We have cloned a region involved in pectate lyase and cellulase secretion by complementation of non-secretory outJ mutants of E. chrysanthemi strain 3937 using the RP4::miniMu plasmid pULB110. The cloned region maps near the ade-22 marker on the E. chrysanthemi 3937 chromosome. An R-prime containing a chromosomal DNA insert of about 30kb was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…carotovora 71, however, indicate a fundamental difference in the arrangement of these genes in E. carotovora and E. chrysanthemi. Previous work with E. chrysanthemi has demonstrated that at least three diaferent chromosomal loci control the Out phenotype (22,23,43,45). The data presented here strongly suggest a clustering of the out genes …”
supporting
confidence: 62%
“…carotovora 71, however, indicate a fundamental difference in the arrangement of these genes in E. carotovora and E. chrysanthemi. Previous work with E. chrysanthemi has demonstrated that at least three diaferent chromosomal loci control the Out phenotype (22,23,43,45). The data presented here strongly suggest a clustering of the out genes …”
supporting
confidence: 62%
“…This information will be important for us to understand whether Ca2+ is required for translocation of PL from cytosol to periplasm or from periplasm to culture fluids. In Erwinia chrysanthemi (5) and P. viridiflava (24), the genes (out) controlling the export of PL have been identified, and one of them has recently been cloned and characterized (13 support the notion that divalent ions play a role in regulation of extracellular enzyme production, none of the foregoing studies included experiments to determine whether the increase in enzyme production is due to the improvement in enzyme-exporting efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The kdgTger\e, coding for the KDG permease is located near ogl and kduD (Allen et al, 1989). The gene outJ, involved in the specific export of pectinases and cellulases toward the external mediunn, is located between ade-377 and the pro locus (Ji et al, 1989). We recently isolated Mu-lac (Km") insertions in the pectinolytic enzyme genes pelD, peIC and pme in strain 3937 (N. Hugouvieux-Cotte-Pattat, submitted for publication).…”
Section: Location Of Genes Invoived In Pectinoiysismentioning
confidence: 99%